Penerapan Akad Musyarokah Mutanaqisoh pada Bank Syariah - Ratih Ramdhiana; Isfandayani . (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2013)
This study aims to determine the application of the contract Musyarakah Mutanaqisoh in Bank Muamalat Indonesia Branch of Rawamangun, East Jakarta. The method used was naturalistic qualitative. The methods of data collection techniques are interviews, documentation, and triangulation. This study proposed to account manager and Unit Support Investment Funds Branch of Bank Muamalat Indonesia Rawamangun, East Jakarta. This study would like to know how applying the contract of musyarokah in Islamic banks, how the implementation of the contract Musyarokah Mutanaqisoh Take Over the mortgage financing in Bank Muamalat Indonesia and how the advantages and disadvantages of the application of the contract Musyarokah Mutanaqisoh in Islamic banks. This research concludes that the implementation of the contract Musyarokah Mutanaqisoh on Islamic banks used to finance mortgages Take Over Bank Muamalat Indonesia Rawamangun Branch Office is in compliance with the rules and regulations of Islamic law related matters Mutanaqisoh Musyarokah theories that have been determined and approved by Dewan Syariah Nasional ( National Shari'a Board).